2022
DOI: 10.1128/spectrum.02137-21
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Human Sweat as a Novel Growth Condition for Clinically Relevant Pathogens on Hospital Surfaces

Abstract: Precise modeling of dry surface biofilms in hospitals is critical for understanding their role in hospital-acquired infection transmission and surface contamination. Using a representative culture condition which includes a nutrient source is key to developing a phenotypically accurate biofilm community. This will enable accurate laboratory testing of cleaning products and their efficacy against dry surface biofilms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 74 publications
(97 reference statements)
0
3
0
Order By: Relevance
“…Previous studies have demonstrated that skin commensals utilize nutrients available on the skin, for example, through the lipase-mediated degradation of sebum lipids by Cutibacterium acnes to promote bacterial adherence ( 7 9 ), the enzymatic cleavage of sphingomyelin to promote barrier integrity and microbial colonization ( 2 ), and the presumed incorporation of lipids into the bacterial cell envelope ( 10 , 11 ). Furthermore, recent efforts to study skin-associated pathogens in synthetic skin-like media versus traditional rich media have revealed that the observed phenotypes are highly dependent on the medium type ( 12 , 13 ). Therefore, the use of culture conditions that mimic those of the human skin is critical for translating findings between the laboratory setting and the native skin environment.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that skin commensals utilize nutrients available on the skin, for example, through the lipase-mediated degradation of sebum lipids by Cutibacterium acnes to promote bacterial adherence ( 7 9 ), the enzymatic cleavage of sphingomyelin to promote barrier integrity and microbial colonization ( 2 ), and the presumed incorporation of lipids into the bacterial cell envelope ( 10 , 11 ). Furthermore, recent efforts to study skin-associated pathogens in synthetic skin-like media versus traditional rich media have revealed that the observed phenotypes are highly dependent on the medium type ( 12 , 13 ). Therefore, the use of culture conditions that mimic those of the human skin is critical for translating findings between the laboratory setting and the native skin environment.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, artificial sweat has been employed in the study of biofilm formation by other clinically-relevant pathogens, including S. aureus, and in the culture of mixed skin microbial communities (13,14). These studies demonstrate that results obtained from laboratory experiments are dependent upon growth conditions, which can vary drastically between the lab setting and the native skin environment.…”
Section: Introductionmentioning
confidence: 97%
“…demonstrate that the emerging pathogen and skin colonizer Candida auris forms dense multilayer biofilms in synthetic sweat, as compared to routine culture media, providing evidence for how the pathogen persists and spreads in hospital settings (12). Similarly, artificial sweat has been employed in the study of biofilm formation by other clinically-relevant pathogens, including S. aureus , and in the culture of mixed skin microbial communities (13, 14). These studies demonstrate that results obtained from laboratory experiments are dependent upon growth conditions, which can vary drastically between the lab setting and the native skin environment.…”
Section: Introductionmentioning
confidence: 99%